2017
DOI: 10.1177/1010428317694324
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated calcium signal transducer 2 regulates neovascularization of non-small-cell lung cancer via activating ERK1/2 signaling pathway

Abstract: Lung cancer, especially the non-small-cell lung cancer, is a highly aggressive vascular cancer with excessively activated signaling pathways. Tumor-associated calcium signal transducer 2, also known as trop2, was identified to be correlated with tumor proliferation and invasion of non-small-cell lung cancer; however, the biological role of trop2 in neovascularization of non-small-cell lung cancer remained elusive. In this study, we first verified that trop2 was overexpressed in non-small-cell lung cancer tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Hence, MVD is considered as an independent prognostic factor in multiple molecular subtypes of breast cancer (Kraby et al, 2017). In the current work, Trop2 expression was significantly correlated with MVD, a finding that was consistent with Ninga, b et al (2013) and Guo et al (2017) who detected a positive correlation between Trop2 expression and tumor neovascularization in cholangiocarcinoma, glioma and non-small cell lung cancer (NSCLC), respectively. The exact mechanisms and factors enhancing pathological tumor angiogenesis are still unclear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, MVD is considered as an independent prognostic factor in multiple molecular subtypes of breast cancer (Kraby et al, 2017). In the current work, Trop2 expression was significantly correlated with MVD, a finding that was consistent with Ninga, b et al (2013) and Guo et al (2017) who detected a positive correlation between Trop2 expression and tumor neovascularization in cholangiocarcinoma, glioma and non-small cell lung cancer (NSCLC), respectively. The exact mechanisms and factors enhancing pathological tumor angiogenesis are still unclear.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is suggested that binding of vascular endothelial growth factor (VEGF) to its receptors stimulates intracellular pathways including extracellular signal-regulated kinase (ERK) and phosphatidyl inositol3 kinase (PI3K), which in turn enhance angiogenic switch in several malignancies including breast cancer (Taneja et al, 2010). Guo et al (2017) reported that Trop2 can stimulate angiogenesis in NSCLC via activation of extracellular signal-regulated kinase /mitogen-activated protein kinase (ERK/MPAK) pathway. Moreover, they demonstrated a reduction of angiogenic markers (CD31, CD34) expression and Ki67 proliferation index after silencing Trop2 gene in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in order to understand the DEGs action mode, we adopted KEGG analysis, which was based on clustering similar genes into a same network, interestingly, the main action modes were cytokine–cytokine receptor interaction and transcriptional misregulation, the related signaling pathways were phosphoinositide 3-kinase (PI3K)-Akt, tumor necrosis factor (TNF), mitogen-activated protein kinase (MAPK), nuclear factor kappa B (NF-κB), RIG-I-like receptor, and Toll-like receptor (Table 2), which were consistent with previous studies in lung cancer. 1416…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-associated calcium signal transducer 2 regulates neovascularization of non-small-cell lung cancer by activating the ERK1/2 signaling pathway (31). In addition, novel calcitonin gene-related peptide/chitosan-strontium-calcium phosphate cement enhances the proliferation of HUVECs (41). Furthermore, increasing extracellular Ca 2+ significantly triggers TNF-α-induced vascular cell adhesion molecule 1 activation and monocyte adhesion in HUVECs (42).…”
Section: Discussionmentioning
confidence: 99%